Ground calibration tests of the laser altimeter (LIDAR) for MMX mission - Hiroki Senshu; Takahide Mizuno; Toru Nakura; Ryo Suetsugu; Kaito Kasai; Hirokazu Ikeda; Hirotomo Noda; Koji Matsumoto; Hiroshi Araki; Kazuhiro Umetani; Akihiro Konishi; Sho Sasaki; et al. (Progress in Earth and Planetary Science)
Abstract The spacecraft for the Japanese Martian Moon eXploration mission is equipped with a LIDAR laser altimeter. The slant range continuously measured by the LIDAR is used for the correction of the local topography and the orbit and attitude of the spacecraft. The channel and gain setting of the LIDAR in the proximity phase will be automatically controlled based on the received energy. This paper reports the result of ground-based calibration tests. The calibration function is obtained for each channel and gain settings. Then, the performance test of the auto gain control function is carried out by changing the received energy gradually. This test demonstrates that the automatic gain control system of the LIDAR works well and the obtained slant range and received energy change smoothly.